Construction of Female Sexuality in Sexting Activity - Victorius Paskah; Dr. Hapsari Dwiningtyas, S.Sos, MA (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2017)
Development of ways of communicating direct the community about what is being communicated. The ease of communication that can now be done quickly and not only sending the text has been made public, especially young people to communicate different messages such as sexting activity. Where in the activities that typically occur sexually suggestive pictures of exchange between men and women. This study aims to determine the construction of female sexuality in sexting activity. Through a phenomenological approach, this study refers to the interpretive paradigm. This study uses the theory foundation of Self-Objectification and Social Exchange Theory. The results of this study indicate that the activity of sexting is usually done by a partner in a dating relationship. Men in sexting activity known to always be the initiator of doing sexting. Usually men ask sexually suggestive images of women to masturbate because it was unable to meet with their partner. But it did not happen in women, women in the study known to never ask sexually suggestive images to masturbate. Sexting behavior is often accompanied by behavioral spreading the sexually suggestive pictures, men in this study are known to be the only party that did the spread of it. While women have always delete the sexually suggestive pictures she has received for fear if the image was known by others, and then consider them as a woman who behaves badly. The study also revealed that praise in sexting activity plays an important role. Men known to always praise sexually suggestive images being sent by a woman. Women on the other hand feel happy if the pictures they send praise, it also encourages them to send the picture again. Women in a patriarchal culture has internalized the value of the subject itself or in other words, has made itself the object which therefore requires an appreciation (praise). The study also revealed that there are differences regarding sexually suggestive pictures sent in by a woman and sent by men. When asked to send a sexually suggestive images it sends an image that shows the entire body, but when men send pictures it sends images showing genitals only. In this study, women never send a picture before his partner (male) asked him to do so. Although women were aware of the risk of the spread of the images, they still gave it because they feel responsible to satisfy the desires of their partner (male).